CLARIFYING THE NOMENCLATURE AND TAXONOMY OF GAGEA KUNAWURENSIS (ROYLE) GREUTER (LILIACEAE) AND ALLIED TAXA - Zarrei, M.; Wilkin, P.; Noltie, H. J.; Ingrouille, M. J.; Chase, M. W. (Edinburgh Journal of Botany, 2011)
Study of relevant types has led to the conclusion that Gagea kunawurensis (Royle) Greuter (Liliaceae) is the correct name for what has recently been known as G. stipitata Merckl. ex Bunge; that G. gageoides (Zucc.) Vved. is the correct name for G. persica Boiss., and that G. kashmirensis Turrill should be reduced to synonymy of G. tenera Pascher. Anatomical and morphological data are presented for these and the related species Gagea dschungarica Regel and G. afghanica A.Terracc., and a key given to allow their discrimination.